2003
DOI: 10.1211/002235702586
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationship determination within a group of substituted phenyl sulfamate based compounds against the enzyme oestrone sulfatase

Abstract: The enzyme oestrone sulfatase (ES) is responsible for the conversion of the stored (sulfated) form of oestrogens to the active form, namely oestrone. In our continuing quest to synthesize potent inhibitors of oestrone sulfatase and to determine the structural requirements for such inhibition, we have synthesized and evaluated several derivatives of phenyl sulfamate. We report the results of the synthesis and biochemical evaluation of a series of 3- and 4-aminosulfonated derivatives of phenol in an effort to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…The purified materials gave C, H, N microanalyses within ± 0.5 of the calculated values except for 1b (N 0.89), 1e (C 0.99) and 1f (C 0.55). Melting points were generally close to the literature values,16,21 and the 1 H NMR and IR spectra were in agreement with their structures. The ACN used in this work was HPLC grade, and Karl Fischer analysis showed that the water content (as a % by volume) in ACN for four samples from different batches was 0.058, 0.048, 0.122 and 0.099.…”
Section: Methodssupporting
confidence: 85%
“…The purified materials gave C, H, N microanalyses within ± 0.5 of the calculated values except for 1b (N 0.89), 1e (C 0.99) and 1f (C 0.55). Melting points were generally close to the literature values,16,21 and the 1 H NMR and IR spectra were in agreement with their structures. The ACN used in this work was HPLC grade, and Karl Fischer analysis showed that the water content (as a % by volume) in ACN for four samples from different batches was 0.058, 0.048, 0.122 and 0.099.…”
Section: Methodssupporting
confidence: 85%